Innate immunity in chemotherapy-induced peripheral neuropathy: recent advances - Dong, Nana; Lin, Tongtong (Frontiers in Pain Research, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common dose-limiting side effect in patients undergoing chemotherapy. Many commonly used chemotherapeutic agents simultaneously induce neurotoxicity and modulate the immune system. Emerging evidence highlights a critical role of the innate immune system in the development of various neuropathic pain conditions. As a natural immune defense mechanism formed during phylogenetic evolution, innate immunity elicits a robust response during CIPN pathogenesis. This review summarizes the roles of the innate immune system—including the skin barrier, innate immune cells, and innate immune molecules—in the context of CIPN.